Pathways to Developing Digital Capabilities within Entrepreneurial Initiatives in Pre-Digital Organizations - Robert Keller; Philipp Ollig; Patrick Rövekamp (Business & Information Systems Engineering, 2022)
To enable new digital business models, pre-digital organizations launch entrepreneurial initiatives. However, in developing the required digital capabilities, pre-digital organizations often face challenges as they are marked by the ways they have historically established their organizational identity. Research on how pre-digital organizations can develop digital capabilities remains scarce. This study draws on a single case study to illustrate potential pathways for the development of digital capabilities. Two key characteristics are identified: the source of digital capability development and the set-up of the actors involved. The authors synthesize four possible pathway manifestations, discuss the dynamic nature of pathway combinations, and suggest that managing a portfolio of pathways may be crucial for pre-digital organizations. Therefore, the study contributes to a better understanding of digital transformation in pre-digital organizations. Furthermore, it provides guidance for practitioners to reflect on when deciding which pathways to follow.
Keywords: 000; Digital transformation; Digital capabilities; Pre-digital organizations; Corporate entrepreneurship; Organizational identity